EXPANDING THE SCOPE OF LAND ACQUISITION IN THE JOB CREATION LAW: BETWEEN INVESTMENT ACCELERATION AND LAND RIGHTS PROTECTION - Irsia Khairina, Ghassani (Program Studi Magister Hukum Universitas Malikussaleh, 2026)
The amendment of the land acquisition legal regime through Law Number 6 of 2023 concerning Job Creation has brought fundamental implications to the concept of